Development of a new biocathode for a single enzyme biofuel cell fuelled by glucose - Asta Kausaite-Minkstimiene (Nature Portfolio, 2021)
Abstract In this study, we reported the development of Prussian blue (PB), poly(pyrrole-2-carboxylic acid) (PPCA), and glucose oxidase (GOx) biocomposite modified graphite rod (GR) electrode as a potential biocathode for single enzyme biofuel cell fuelled by glucose. In order to design the biocathode, the GR electrode was coated with a composite of PB particles embedded in the PPCA shell and an additional layer of PPCA by cyclic voltammetry. Meanwhile, GOx molecules were covalently attached to the carboxyl groups of PPCA by an amide bond. The optimal conditions for the biocathode preparation were elaborated experimentally. After optimization, the developed biocathode showed excellent electrocatalytic activity toward the reduction of H2O2 formed during GOx catalyzed glucose oxidation at a low potential of 0.1 V vs Ag/AgCl, as well as good electrochemical performance. An electrocatalytic current density of 31.68 ± 2.70 μA/cm2 and open-circuit potential (OCP) of 293.34 ± 15.70 mV in O2-saturated 10 mM glucose solution at pH 6.0 were recorded. A maximal OCP of 430.15 ± 15.10 mV was recorded at 98.86 mM of glucose. In addition, the biocathode showed good operational stability, maintaining 95.53 ± 0.15% of the initial response after 14 days. These results suggest that this simply designed biocathode can be applied to the construction of a glucose-powered single enzyme biofuel cell.